2022
DOI: 10.1001/jamahealthforum.2021.4752
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Medicaid Enrollment and Disenrollment During the Early Phase of the COVID-19 Pandemic in Wisconsin

Abstract: IMPORTANCEAfter the federal public health emergency was declared in March 2020, states could qualify for increased federal Medicaid funding if they agreed to maintenance of eligibility (MOE) provisions, including a continuous coverage provision. The implications of MOE provisions for total Medicaid enrollment are unknown. OBJECTIVE To examine observed increases in Medicaid enrollment and identify the underlying roots of that growth during the first 7 months of the COVID-19 public health emergency in Wisconsin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 9 publications
3
17
0
Order By: Relevance
“…Taken together, our findings suggest modest improvements in overall insurance coverage within Medicaid expansion states during the COVID-19 pandemic. Our results also comport with prior work suggesting a shift toward public coverage may have blunted pandemic-related losses of employer-sponsored health insurance 23,24. Moreover, these results reinforce the value of Medicaid expansion as one tool to improve access to health insurance and care for marginalized and vulnerable populations, even during intersecting public health and economic crises.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Taken together, our findings suggest modest improvements in overall insurance coverage within Medicaid expansion states during the COVID-19 pandemic. Our results also comport with prior work suggesting a shift toward public coverage may have blunted pandemic-related losses of employer-sponsored health insurance 23,24. Moreover, these results reinforce the value of Medicaid expansion as one tool to improve access to health insurance and care for marginalized and vulnerable populations, even during intersecting public health and economic crises.…”
Section: Discussionsupporting
confidence: 85%
“…Consequently, the increase in Medicaid enrollment is attributable to greater continuity of existing coverage in addition to an influx of new enrollees. 24 …”
Section: Discussionmentioning
confidence: 99%
“…This finding builds on prior work that Wisconsin Medicaid enrollment during the PHE was predominantly due to the continued coverage rather than new enrollees. [15] Our work shows similar results across multiple states. To the extent to which the reduction of enrollment is due to policy changes like FFCRA, policies appear to have reduced instability in Medicaid access and promote continuity of coverage during this time.…”
Section: Resultssupporting
confidence: 72%
“…[ 13 ] Responding to the FFCRA, states extended eligibility for individuals already enrolled in Medicaid who might otherwise have become ineligible. [ 9 , 14 ] Accordingly, a recent study in a single state suggested that Medicaid enrollment during the PHE was largely due to the maintenance of continuous coverage rather than new enrollees due to unemployment [ 15 ] and another study found a significant increase in enrollment for safety net programs during the PHE. [ 16 ] However, analyses have not assessed the relative importance of increased new enrollment as compared with reduced disenrollment as drivers of increased total enrollment.…”
Section: Introductionmentioning
confidence: 99%
“…This churning (exiting and then re-entering the program) has been associated with disruptions in access to care and negative health outcomes. 3 In their study published in JAMA Health Forum, Dague and colleagues 4 used Medicaid administrative data from Wisconsin to decompose whether increases in the state's Medicaid enrollment were driven by the FFCRA continuous coverage provisions or by the economic disruptions brought on by the pandemic. This analysis is timely and important for policy makers: the former (FFCRA provisions) would suggest states may experience a sharp spike in disenrollment when the PHE ends, rather than gradual changes in coverage as the economy improves.…”
mentioning
confidence: 99%